2021
DOI: 10.1097/mat.0000000000001534
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coatings for Rotary Ventricular Assist Devices: A Systematic Review

Abstract: Rotary ventricular assist devices (VADs) are frequently used to provide mechanical circulatory support to patients suffering from end-stage heart failure. Therefore, these devices and especially their pump impeller and housing components have stringent requirements on wear resistance and hemocompatibility. Various surface coatings have been investigated to improve the wear resistance or hemocompatibility of these devices. The aim of the present systematic review was to build a comprehensive understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…The adhesion and aggregation of platelets on the surface of materials can also activate platelets and lead to coagulation. Better blood contact materials (such as vascular catheters) must not only inhibit the adsorption of non-speci c proteins in the blood and lower hemolysis rates but also effectively inhibit platelet adhesion, aggregation, and activation (52,55,56). There was no difference in the amount of platelet deposition adhered to the inner surface of the PTFE-SiO 2 and PTFE-IC@dMSNs catheter, but it was signi cantly reduced compared to the PTFE catheter.…”
Section: In Vitro Blood Compatibilitymentioning
confidence: 99%
“…The adhesion and aggregation of platelets on the surface of materials can also activate platelets and lead to coagulation. Better blood contact materials (such as vascular catheters) must not only inhibit the adsorption of non-speci c proteins in the blood and lower hemolysis rates but also effectively inhibit platelet adhesion, aggregation, and activation (52,55,56). There was no difference in the amount of platelet deposition adhered to the inner surface of the PTFE-SiO 2 and PTFE-IC@dMSNs catheter, but it was signi cantly reduced compared to the PTFE catheter.…”
Section: In Vitro Blood Compatibilitymentioning
confidence: 99%
“…It is estimated that there are more than 5.8 million heart failure patients in the USA with a 30-day mortality rate of 11%, a hospitalization rate of ~25%, and a 5-year survival time worse than most cancers [3]. Aside from that, there are 15 million patients in Europe who account for 45% of deaths [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies addressing wear-resistant coatings for VADs via preparation at VADs-friendly temperature based on our recent systematic review on coatings for VADs. 9 Diamond-like carbon (DLC) films, with excellent wear resistance, good mechanical properties, haemocompatibility, and biocompatibility, [10][11][12] can be desirable for surface modification of Ti6Al4V used for VADs manufacturing. Łępicka et al 13 analyzed the coefficient of friction time series of non-coated and DLC-coated Ti6Al4V acquired during tribological tests, and confirmed that the DLC films could reduce wear of Ti6Al4V alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, it is of high practical value to develop wear‐resistant coatings for VADs under the magnets‐tolerable temperatures. However, there are few studies addressing wear‐resistant coatings for VADs via preparation at VADs‐friendly temperature based on our recent systematic review on coatings for VADs 9 …”
Section: Introductionmentioning
confidence: 99%